Marketing Mix Factors for Promoting Tourism of Tourists in Doi Phukha National Park, Nan Province - Netithammakun, Yuphayong; Putachote, Nitipon (NEU ACADEMIC AND RESEARCH JOURNAL, 2024)
Tourism is considered as a major engine driving the Thai economy. The research purposes (1) to study the personal factors and behavior of tourists in Phu Kha National Park, Nan Province; (2) to study the factors of marketing mix for tourism among tourists in Phu Kha National Park, Nan Province; and (3) to compare the differences between personal factors and tourism behavior with satisfaction in factors of marketing mix , and the findings were used to develop tourism strategies in Phu Kha National Park, Nan Province, based on marketing mix principles. The research used a quantitative method, and data were collected using a structured questionnaire to gain the information from 400 tourists. The statistics used included percentages, averages, standard deviations. The results shown that (1) most of the sample population were men, and graduated from high school or vocational education. They were self-employed or run their own businesses, and be married which had an average monthly income of 15,001-20,000 baht. Regarding to the ecotourism behavior, most sample respondents brought their families or friends when they went to the park. They participated in activities by the national park, they usually travelled on holidays or religious festivals, they surfed the information from websites and social media for making decision, and they travelled by their private cars. (2) the factors of marketing mix on the promotion and service environment were in the highest level. Therefore, the researcher suggests that Phu Kha National Park should organize activities and proactively promotes the park through the social media, particularly targeting self-employed individuals who have high purchasing power and rely on online information for decision-making.